Rare bird documentation form for Lesser Black-backed Gull at Lock and Dam 15, 1995 - Fuller, James Let al (1995)
Rare bird documentation form for a Lesser Black-backed Gull at Lock and Dam 15 in Scott County, IA on February 5, 1995 and February 12, 1995. Epson - sheet feed